Data for: The cost-effectiveness of Covid-19 vaccination in age groups children, adults and elderly in Europe – A systematic review - Untung, Tanto; Johansson, Pia (University of Gothenburg, 2024)
The data set is support documentation for planned publication with the title "The cost-effectiveness of covid-19 vaccination in age groups children, adults and elderly in Europe – A systematic review."
The systematic review aimed to identify empirical evidence of the cost-
effectiveness of Covid-19 vaccination programs within European countries
among elderly and adult age groups. The result further acted as a parameter to
assess the cost-effectiveness of a similar program in Sweden.

The content of data set are:
1. Search strategy of screening process (7 files)
2. Quality assessment forms (4 files)
3. Data extraction list (2 files)
4. Exclusion list (1 file)
5. PRISMA flowchart (1 file)
6. Table of estimation QALY lost/averted death (1 file)
7. QALY comparison (4 files)

Datasetet är tillhörande dokumentation för en planerad publikation av typen systematisk översikt med titeln "The cost-effectiveness of covid-19 vaccination in age groups children, adults and elderly in Europe – A systematic review".
Den systematiska översikten hade som syfte att identifiera empiriskt bevis för kostnadseffektiviteten av Covid-19 vaccinationsprogram inom europeiska länder bland åldersgrupperna äldre och vuxna. Resultatet användes som en parameter för att utvärdera kostnadseffektiviteten av liknande program i Sverige.

Data innehåller följande filer:
1. Search strategy of screening process (7 filer)
2. Quality assessment forms (4 filer)
3. Data extraction list (2 filer)
4. Exclusion list (1 fil)
5. PRISMA flowchart (1 fil)
6. Table of estimation QALY lost/averted death (1 fil)
7. QALY comparison (4 filer)
Data för: The cost-effectiveness of Covid-19 vaccination in age groups children, adults and elderly in Europe – A systematic review
Keywords: CHILDREN; BARN; Age Groups; Åldersgrupper; ELDERLY; ÄLDRE; ADULTS; VUXNA; Vaccination; Vaccination; Health Care Economics and Organizations; Hälso- och sjukvårdsekonomi och organisationer; Covid-19; Covid-19 (virus påvisat); Medication and treatment; Medicinering och behandlingar; Specific diseases, disorders and medical conditions; Specifika sjukdomar, störningar och medicinska tillstånd; Public health; Folkhälsa; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin; Epidemiology; Epidemiologi